JURIDICAL REVIEW AGAINST REJECTION OF PEACE IN THE CASE OF BONDED COMPANY - Alfitra Rinaldo; Hasnati; Indra Afrita (JILPR Journal Indonesia Law and Policy Review, 2021)
Parties who take the initiative to apply for PKPU are generally debtors, namely debtors who are unable or expected to be unable to continue paying their debts, PKPU requests can also come from creditors who have calculated that the debtor will no longer be able to pay the debt. -the debt. The formulation of the problem in this research is how is the juridical review of the bankrupt company, how is it?Juridical Review of Refusal of Peace in Bankrupt Companies, and howLegal Consequences of Refusal of Reconciliation in Cases of Bankrupt Companies. The purpose of this study is to analyze the juridical review of the bankrupt company, to analyze the Juridical Review of Refusal of Peace in Bankrupt Companies, and To Analyze Legal Consequences of Refusal of Reconciliation in Cases of Bankrupt Companies.This research method is normative legal research. The conclusion in this study has answered the problems that arise, namely the Juridical Review of Bankrupt Companies that companies that have problems in their ability to fulfill their debt obligations take various alternative settlements. They can negotiate a request for debt relief, either in part or in full. They can also sell some of their assets or even their business, they can also convert the loan into equity participation, besides the possibility that the company can also negotiate a request for a postponement of debt repayment obligations as a final solution, then a solution is taken through the bankruptcy process if the peace process is not reachedJuridical Review of Refusal of Peace in Bankrupt Companies that Peace in bankruptcy is the right of the bankrupt debtor to file it. Legal Consequences of Refusal of Reconciliation in Cases of Bankrupt Companies that the continuation of the debtor's business due to the refusal of reconciliation is still possible in order to increase or at least maintain the value of the debtor's assets. The proposal to continue a bankrupt debtor company must be accepted if it is approved by the creditor representing ½ of all recognized and temporarily accepted receivables.